Analisis Disparitas Pendapatan di Kawasan Pariwisata, Kecamatan Kuta, Kabupaten Badung - Dian Sri Apriliani, Ni Kadek; Bendesa, I. K. G. (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 4, April 2013 (pp. 173-225), 2013)
Industrial development, especially in the tourism industry in general in Bali and Kuta district in particular in the present is already highly developed. Each year millions could both local and international travelers coming to visit. On the other hand, fishermen or farmers still persist even engaged in it is not too much. The purpose of this study is to determine the presence or absence of income inequality among tourism workers and fishermen or farmers. The research was conducted in the Kuta district, Badung regency using a sample of 98 people. The analysis technique used is the Gini index based on the geometric definition. The results obtained showed the income inequality between workers and peasants of 0.331 tourism, among farmers at 0.111, and 0.184 for tourism among workers. From these results it means that income inequality that occurred in the district of Kuta including low inequality.
Keywords: tourism , farmers , indexs Gini , inequality